Using virtual reality to assess gesture performance deficits in schizophrenia patients - Pavlidou, Anastasia; Gorisse, Geoffrey; Banakou, Domna; Walther, Sebastian (Frontiers in Psychiatry, 2023)
Introduction Gesture performance deficits are prevalent in schizophrenia patients and are strongly associated with poor social communication skills and community functioning, affecting their overall quality of life. Currently, video-recording technology is widely used in clinical settings to assess gesture production deficits in schizophrenia patients. Nevertheless, the subjective evaluation of video-recordings can encumber task assessment. The present study will aim to use virtual reality to examine its potential use as an alternative tool to objectively measure gesture performance accuracy in schizophrenia patients and healthy controls. Methods Gesture performance in the virtual reality setting will be based on the well-established Test of Upper Limb Apraxia. Participants will be immersed in a virtual environment where they will experience themselves being embodied in a collocated virtual body seen from a first-person perspective. Motion trackers will be placed on participants’ hands and elbows to track upper body movements in real-time, and to record gesture movement for later analysis. Participants will see a virtual agent sitting across from them, with a virtual table separating them. The agent will perform various types of gestures and the participants’ task will be to imitate those gestures as accurately as possible. Measurements from the tracking devices will be stored and analysed to address gesture performance accuracy across groups. Discussion This study aims to provide objective measurements of gesture performance accuracy in schizophrenia patients. If successful, the results will provide new knowledge to the gesture literature and offer the potential for novel therapeutic interventions using virtual reality tools. Such interventions can improve gesturing and thus advance social communication skills in schizophrenia patients.